Changes On Essential Oil Composition of Aniseed (Pimpinella anisum L.) During Ten Maturity Stages - Ozel, Abdulhabip (Asian Journal of Chemistry, 2010)
The essential oils extracted from aniseeds at ten different maturation stages were analyzed by GC-FID. The essential oil contents of the aniseed (2.38-4.60 %, v w-1) showed remarkable variations during maturation. At the later maturation stages, the essential oil contents of aniseed decreased. A total 20 compounds were detected in the samples representing 93.34- 97.31 % of the total essential oils. The (E)-anethole rates were found in between 85.14-92.28 % and the (E)-anethole was the main component of aniseed at all stages of harvesting. The obtained results indicate that the aniseed should be harvested at the 1st, 2nd or 3rd maturation stages, since the levels of both essential oils and (E)-anethole are the highest. If this is not the case, the 6th maturation stage should be considered as the appropriate harvesting period.